1990
DOI: 10.1038/bjc.1990.30
|View full text |Cite
|
Sign up to set email alerts
|

The response of cerebral metastases in small cell lung cancer to systemic chemotherapy

Abstract: Summary Although small cell lung cancer (SCLC) is very chemosensitive, cerebral metastases are treated with radiotherapy in the belief that they are protected from chemotherapy by the blood-brain barrier (BBB). The validity of this assumption has not been tested in clinical practice. In a randomised trial of treatment in 610 patients with SCLC, 19 patients who had symptomatic cerebral metastases at presentation were treated initially with chemotherapy, and cranial irradiation withheld. (Long et al., 1979). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(17 citation statements)
references
References 19 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…No patient developed clinical or radiological evidence of CNS disease during chemotherapy. This observation fits with recent reports suggesting that chemotherapy is effective in the treatment of cerebral metastases from SCLC (Kantarjian et al, 1984;Twelves et al, 1990; and that the response rate at this site is the same as at other extra-cranial sites of disease (Twelves et al, 1990). Despite these encouraging observations, it is unlikely that maintenance chemotherapy would significantly delay the development of CNS disease since resistance would be anticipated here as at other sites.…”
Section: Discussionsupporting
confidence: 51%
“…No patient developed clinical or radiological evidence of CNS disease during chemotherapy. This observation fits with recent reports suggesting that chemotherapy is effective in the treatment of cerebral metastases from SCLC (Kantarjian et al, 1984;Twelves et al, 1990; and that the response rate at this site is the same as at other extra-cranial sites of disease (Twelves et al, 1990). Despite these encouraging observations, it is unlikely that maintenance chemotherapy would significantly delay the development of CNS disease since resistance would be anticipated here as at other sites.…”
Section: Discussionsupporting
confidence: 51%
“…[36][37][38][39] However, only small numbers of patients were enrolled in each phase II trial. Most of the studies were based on cisplatin or etoposide, but other agents included cyclophosphamide, vincristine, or doxorubicin.…”
Section: Breast Cancer (Table 2)mentioning
confidence: 99%
“…Chemosensitive tumors such as SCLC have been shown by multiple authors to have a high percentage of initial responders using multiagent chemotherapy [17]. For example, Krisjansen et al [18•] reported similar results in patients with SCLC treated with the combination of CDDP, etoposide, and vincristine.…”
Section: Treatment Difficultiesmentioning
confidence: 63%